Identification of Immmunogenic Salivary Proteins of Anopheles vagus based on Mass Spectrometry Analysis - Febriyantiningsih, Dwi Esti; Senjarini, Kartika; Oktarianti, Rike (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2017)
Malaria has been prevalent for a long time in tropical developing regions causing great morbidity and mortality. Among the malaria vectors, Anopheles vagus has been known as secondary malaria vector in East Java. Salivary glands of mosquitoes perform various functions for survival of the vectors and also conducive for blood feeding, harbouring of malaria parasites, and eventual parasite transmission. The salivary gland proteomes of An. vagus have not been carried out yet. The aim of our study was to identify and characterize the immunogenic proteins of salivary glands proteins of An. vagus. A proteomic approach combining one-dimensional electrophoresis (1DE) followed by western blot analysis using human sera from healthy people living in an endemic area (Kendal); liquid chromatography mass spectrometry (LC-MS/MS) and bioinformatic analysis was adopted to provide the first direct insight into identification and characterization of salivary proteins of An. vagus. Identification of immunogenic proteins using western blot analysis has revealed three immunogenic bands which had molecular weights of 69, 75 and 232 kDa. Among those proteins analysed by LC-MS/MS, there were alpha,1-4 glucan phosphorylase, putative myosin class I heavy chain which have the highest number of total spectrum count peptide. Other proteins like vitellogenin and heat shock protein 82 (Hsp82) were also identified. The majority of proteins were scrutinized marked for their role in metabolism, cytoskeleton protein and stress response. Keywords: Anopheles vagus, salivary gland, immunogenic, proteomics